Uncovering Alleged Hate Speech in Ahmad Dhani's Statements: A Forensic Linguistic Study - Harto Malik; Jefriyanto Saud (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study delves into hate speech instances within social media statements by Ahmad Dhani Prasetyo (ADP) using forensic linguistic analysis. Leveraging advanced data mining techniques, relevant data was extracted from ADP's Twitter account. Through meticulous lexical, grammatical, and pragmatic analysis, expressions of hate speech and defamation within these online statements were identified and categorized. The significant findings offer a comprehensive understanding of hate speech's linguistic features in social media contexts, contributing to forensic linguistics and digital communication discourse. Moreover, practical insights are provided for drafting investigation reports and informing legal decisions and policies regarding online defamation. By emphasizing the importance of linguistic analysis in identifying and addressing hate speech, this research presents a methodological framework applicable to similar cases in the future. Ultimately, this study underscores the broader implications and relevance of linguistic analysis in combating hate speech in digital platforms, paving the way for future research directions and applications